Social Business Model Innovation: A Quadruple/Quintuple Helix-Based Social Innovation Ecosystem - Carayannis, Elias G.; Grigoroudis, Evangelos; Stamati, Dimitra; Valvi, Theodora (IEEE Transactions on Engineering Management, 2021)
Social innovation is related to new products, services, and models aiming to improve human well-being and create social relationships and collaborations. The business model innovation (BMI) context can foster social innovation and can be applied in social innovation projects and initiatives. What is important for social BMI is the social mission, which needs to be defined in order to be able to move forward with the strategy, the value proposition, and the best practices of the business. Based on the existing social innovation literature and case studies, this paper proposes an “ecosystem” approach that can provide an integrated framework for social business models. This approach adopts the quadruple/quintuple helix innovation models which are able to promote social innovation, enabling a locus-centric and triple-bottom-line-centric entrepreneurial process of knowledge discovery and exploitation. Such a framework may help to study the role, nature, and dynamics of social co-opetitive fractal ecosystems, given emphasis on civil society, political structures, environment, and sustainability. In addition, the social innovation case studies presented in this paper highlight that targeted open innovation is a key element for social BMI.
Conference Name: IEEE Transactions on Engineering Management
Keywords: Développement durable; Entreprise sociale; Innovation sociale; Modèle; Quadruple helix approach; Réservé UdeM